Dietary supplementation of milk powder can enhance the gonad development in African catfish, Clarias gariepinus - Siti Nor Fatihah; Nur Farisha Shawal Tul Masri; Nur Hidayah Nazari; Muhammad Wathiq Rifqee Anuar; Lim, Leong Seng (Pusat Penyelidikan dan Inovasi, 2021)
Pellets are most important for growth of aquatic fish and pellets with high in protein can help in every internal development. There are many types of pellets with different protein content, but for this study it focusses on brood stock pellet with content of 28-30 % protein. The study was focus on the brood stock of C. gariepinus catfish with observations on the gonads of brood stock. The objective was to identify the effectiveness of pellet for gonad maturity in male and female of C. gariepinus. Three tanks were used in the study and each tank was placed 1 male and 2 females. The duration of experiment was 30 days and C. gariepinus were fed with commercial pellet, 5% pellet with addition of milk (M5) and 10% pellet with addition of milk (M10). The study showed M5 was more successful than M10 and commercial pellets because of based on the color of the gonad in C. gariepinus. From the gonad weight, M5 (45.0 g) have heavier gonads than M10 (43.0 g) and commercial pellets (20.3 g). As a conclusion, pellets with addition of milk can be used in female of C. gariepinus for gonad development and artificial breeding.